204 The effects of fatigue induced by high intensity soccer-specific simulation on jump-landing mechanics and functional hamstrings to quadriceps ratio in youth players. (3rd March 2020) - Mohammed Firhad Raja Azidin, Raja; Bukry, Saiful Adli; Manaf, Haidzir; Justine, Maria; Hasan, Hosni; Ismail, Hashbullah; Sharir, Raihana
Abstract : Background: High incidence of non-contact anterior cruciate ligament (ACL) injuries were reported in youth soccer player. Most injuries occur in the latter stages of match-play, which may be attributed to match related fatigue. Objective: To investigate the influence of fatigue on markers of ACL injury risks related jump-landing mechanics and functional hamstring to quadriceps (HQ) ratio in youth players. Design: Single-group repeated measures design. Setting: Recreationally trained youth soccer players in Malaysia. Patients (or Participants): Twenty male youth soccer players (16±0.9 years) were recruited in this study. Interventions (or assessment of risk factors): A 5-min high intensity soccer-specific fatigue simulation developed for youth players were utilised. Biomechanical risk factors were assessed using Landing Error Scoring System (LESS). Peak torques of quadriceps concentric (Qcon) and hamstrings eccentric (Hecc) contractions were recorded using an isokinetic dynamometer. Main outcome measurements: All players completed the fatigue simulation twice. Prior to simulation (time 0 min), immediately after simulation (time 5 min), 15 min (time 20 min) and 30 min (time 35 min) post-simulation players were tested for either five trials of jump landing task (LESS), or five maximal dominant limb isokinetic contractions for Qcon and Hecc. A one-way ANOVA repeated measures was used to identify significant differences, with α=0.05. Results: A significant increase in total LESS score (higher risk) were observed over time (F1.7, 33.7=62.3, P<0.001). Hecc contraction significantly reduce at time 5 min (P=0.005) and time 20 min (P=0.032). There were no significant changes in Qcon and functional HQ ratio after simulation. Conclusions: These findings suggest a greater risk of ACL injury in male youth players during fatigue as a consequence of improper jump-landing mechanics and eccentric hamstrings strength impairments. Future studies are needed to explore the potential of injury prevention program and return to play assessments that include jump-landing tasks, isokinetic strength and fatigue simulation for youth soccer player.